Effect of disease duration on the association between serum albumin and mucosal healing in patients with ulcerative colitis. Issue 1 (7th June 2021) - Yagi, Sen; Furukawa, Shinya; Shiraishi, Kana; Hashimoto, Yu; Tange, Kazuhiro; Mori, Kenichirou; Ninomiya, Tomoyuki; Suzuki, Seiyuu; Shibata, Naozumi; Murakami, Hidehiro; Ohashi, Katsuhisa; Hasebe, Aki; et al.
Abstract : Objective: Serum albumin is used as a marker of acute inflammation. Several studies have addressed the association between serum albumin and clinical outcome in patients with ulcerative colitis (UC). While mucosal healing (MH) has been indicated as the therapeutic goal for UC, the association between serum albumin and MH remains unclear. We evaluated this issue in patients with UC overall and explored whether duration of UC affected this association. Design: This cross-sectional study recruited consecutive patients with UC. Study subjects consisted of 273 Japanese patients with UC. Serum albumin was divided into tertiles based on its distribution in all study subjects. One endoscopy specialist was responsible for measuring partial MH and MH, which were defined as a Mayo endoscopic subscore of 0–1 and 0, respectively. The association between serum albumin and clinical outcomes was assessed by multivariate logistic regression. Results: Rates of clinical remission, partial MH and MH were 57.9%, 63% and 26%, respectively. Only high serum albumin (>4.4 mg/dL) was significantly positively associated with MH (OR 2.29 (95% CI: 1.03 to 5.29), p for trend=0.043). In patients with short UC duration (<7 years) only, high serum albumin was significantly positively associated with MH and clinical remission. In patients with long UC duration (≥7 years), in contrast, no association between serum albumin and clinical outcomes was found. Conclusion: In Japanese patients with UC, serum albumin was significantly positively associated with MH. In patients with short UC duration, serum albumin might be a useful complementary marker for MH.